Loyalty Programs in Czechia, Slovakia, and Russia - Tahal, Radek; Formanek, Tomas (Indian Journal of Marketing, 2016)
Establishing and curating customer loyalty is an ever more important feature of contemporary marketing. In order to strengthen this aspect, companies frequently develop specialized loyalty programs. This paper aimed to provide better understanding of this topic by means of quantitative analysis of consumers’ socio - demographic and lifestyle factors influencing the participation in loyalty programs. In this study, we addressed diverse types of loyalty programs and different types of product categories. This paper compared and put into context information on customer behaviour in three countries: our research is based on primary data collected in Czechia, Slovakia, and Russia. We provided a detailed and empirically oriented interpretation of the results obtained. At the same time, the tables with summarized output would allow readers to draw their own conclusions, given the socio - demographic or product category of interest. New information concerning customer loyalty programs is presented, which may be utilized both in further academic research and in business marketing.